Editorial - Editor, Journal (University of Dar es Salaam Library Journal, 2018)
We would like to inform our esteemed readers that there have been some changes in the issuance of our journal. Whereas in the past we used to have both online and print versions, this time there will only be an online version. This measure has been taken primarily to cut down on soaring publishing costs. Moreover, full-text articles will be accessed through the African Journal Online (AJOL), the world ' s largest online library of peer-reviewed, African-published scholarly journals. This issue consists of seven articles. Click full text for details.